An EPG and perceptual study of postalveolar and palatal affricate contrast in Standard Croatian - Liker, Marko; Gibbon, Fiona (2012)
In Classical Standard Croatian affricates /ʧ/ and /ʤ/ are traditionally considered postalveolar, while /ʨ/ and /ʥ/ are described as palatal. However, researchers claim that a new sociophonetic norm has emerged in major Croatian cities during the last two decades, whereby postalveolar and palatal affricates are neutralised in the articulatory and acoustic space somewhere between postalveolar and palatal. These conflicting claims are based primarily on subjective listener judgements, however, and there are no recent instrumental studies to support either claim. This study used instrumental and perceptual analyses of nonsense sequences recorded from six speakers who were judged as representative of the new sociophonetic norm. In the instrumental study, electropalatographic (EPG) data were analysed to evaluate whether tongue palate contact data supported the traditional view or the more recent claims regarding Croatian affricates. The EPG results indicated that Croatian affricates were not separated in terms of postalveolar versus palatal place of articulation. Instead, speakers articulated both affricate targets in a similar – alveolar or postalveolar – region of the palate. However, the affricates were not neutralised either because all speakers had significantly higher amounts of contact particularly in the anterior four rows of electrodes for palatal affricate targets. The results of the EPG analysis were supported by the results of the perceptual study. This study involved 28 naïve listeners who were able to identify the overwhelming majority (86%) of affricates accurately. The perceptual and EPG results raised therefore the question of what phonetic features characterise modern Croatian affricates. In this paper, we argue that the EPG data is consistent with the view that speakers use different lingual articulators – apical versus laminal – to articulate these affricates. We speculate that the increased contact associated with laminal articulations enhances the perceptual cues of palatalization that are used by listeners to identify the palatal affricates and thus distinguish them from the postalveolar affricates.
Special issue: Articulatory techniques for sociophonetic research (eds. Chiara Celata & Silvia Calamai)
Projekt MZOS
ENG